2015
DOI: 10.1177/0748730415597519
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Genome Editing via CRISPR/Cas9 to Create Clock Gene Knockout Cells

Abstract: Targeted genome editing using CRISPR/Cas9 is a relatively new, revolutionary technology allowing for efficient and directed alterations of the genome. It has been widely used for loss-of-function studies in animals and cell lines but has not yet been used to study circadian rhythms. Here, we describe the application of CRISPR/Cas9 genome editing for the generation of an F-box and leucine-rich repeat protein 3 (Fbxl3) knockout in a human cell line. Genomic alterations at the Fbxl3 locus occurred with very high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…By targeting the core promoter, e.g. the TATA box, by gene editing techniques [ 73 , 74 ], it might be possible to more precisely attenuate rhythmicity while keeping average levels constant.…”
Section: Discussionmentioning
confidence: 99%
“…By targeting the core promoter, e.g. the TATA box, by gene editing techniques [ 73 , 74 ], it might be possible to more precisely attenuate rhythmicity while keeping average levels constant.…”
Section: Discussionmentioning
confidence: 99%
“…For the generation of a human U87MG A 3 AR Knockout (U87MG KO ) cells we used the CRISPR-Cas9 system [48]. The plasmidial vector contained the Cas9 endonuclease and gRNA was purchased at Santa Cruz Biotechnology (sc-402007).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we devised CSAC, a system of multiplexed sgRNAs targeting core clock components packaged in a single AAV, to abolish molecular clock oscillation by inducing null mutations into several core clock genes. We selected the multiplexed sgRNAs based on leucine-rich repeat protein 3 (Fbxl3) [23] . To do so, they transfected U2-OS cells stably expressing a Bmal1-Luciferase reporter with a lentivirus expressing Cas9 and two sgRNA targeting different sites in the Fbxl3 gene, and found that CRISPR-Cas9-based Fbxl3 KO dampened Bmal1 promoter-driven luminescence oscillation.…”
Section: Discussionmentioning
confidence: 99%
“…In circadian genes, several applications of the CRISPR-Cas9 system has been reported to KO molecular clock components in a robust and efficient manner. Korge et al first utilized CRISPR-Cas9mediated gene targeting in chronobiology to generate FBXL3 KO U2-OS cells [23] and have recently extended this application to generate CRY1 and CRY2 KO U2-OS cells. The CRISPR-Cas9 system has also been used to generate KO animals lacking core clock genes in mice, macaques, monarch butterflies, and Neurospora crassa [24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%